Dissolved organic carbon and nitrogen dynamics in the Douro River estuary, Portugal - C Magalhães; C Teixeira; R Teixeira; A Machado; I Azevedo; AA Bordalo (Ciencias Marinas, 2008)
Dissolved organic carbon (DOC) and dissolved organic nitrogen (DON) are metabolically important in estuaries. Their availability is influenced by organic matter inputs (internal and external) as well as by internal microbial transformations within the system. In this study, spatial and seasonal dynamics of DOC and DON were evaluated in the Douro River estuary (Portugal). Monthly surveys were performed from October 2005 to December 2006 along a salinity gradient at three different depths. DOC and DON were calculated by subtracting the respective inorganic components (dissolved inorganic carbon, DIC, and dissolved inorganic nitrogen, DIN) from total dissolved carbon (TDC) and total dissolved nitrogen (TDN). In the Douro River estuary, DIC exhibits a linear and positive distribution as a function of salinity, indicating an input of DIC into the estuary from coastal waters. This pattern of distribution along the salinity gradient was also observed for total particulate matter, since a decreasing trend upstream was observed. In contrast, the results showed a general nonconservative behaviour of DOC along the estuarine transect during most months. This typical deviation from conservative mixing was mainly associated with sewage DOC sources into the lower and middle estuary. On average, DON concentrations represented 52–88% of the TDN. Along the transect, relationships between DIN and DON with salinity were generally conservative, decreasing towards the mouth, highlighting the fluvial source of such nitrogen forms; however, occasional DON sewage loads were registered. Estimated global Douro River watershed exports of DOC and DON to coastal waters yielded values of 420 kg C m–2 yr–1 and 125 kg N m–2 yr–1, respectively, which are high when compared with previously predicted levels from global models of DOC and DON export.